#TITLE_ALTERNATIVE# - SUKANDAR (NIM 33095009); Promotor: Prof.Dr.Ir. V.S. Praptowidodo dan Dr.Ir. Subagjo, UKAN
Conventionally, enzymatic reactions have been carried out in a batch process by incubating a mixture of substrate and soluble enzyme in a strirred tank bioreactor. In the enzymatic reaction process that categorized into this homogeneous phase reaction system, it is technically very difficult to recover active enzyme from the reaction mixture. Accordingly, even if an enzyme in the reaction mixture still has high catalytic activity, the enzyme is usually not separated for reuse as a biocatalyst. At the end of the conversion process, the enzyme and other contaminating proteins are generally removed by denaturation by pH or heat treatment and discarded. This is uneconomical, as active enzyme is lost after each batch reaction. A promising method for the recovery and reuse of biocatalyst in the form of soluble enzymes is the use of the membrane bioreactor systems. In this bioreactor systems, the membrane is used as a barrier to separate the products stream from the reaction solution containing free enzymes. The enzymes are retained inside the membrane bioreactor, whereas the products permeate through the membrane. The focus of this research is the development of a combined process of membrane, ultrafiltration and electrophoresis for the enhancement of conventional membrane bioreactor for enzyme catalyzed reaction system. This research is based on the hypothesis that the coupling of conventional membrane bioreactor with electrophoresis will enhance the performance of the bioreactor due to (a) the prevention of enzyme polarization on the membrane surface so that the enzyme can be used effectively in the bulk reaction solution, and (b) the stimulation of simultaneous product separation and concentration. In this research, the application of the combined process for the continuous production of 6-aminopenicillanic acid (6-APA) from benzylpenicillin (pen-G) based on homogeneous hydrolysis reaction catalyzed by penicillin acylaseenzyme in a novel ultrafiltration membrane bioreactor was studied. In particular, this research is directed to study the effect of the electrophoresis of enzyme and charged molecules on the performance of membrane bioreactor. In the absence of electrophoresis, the continuous production of 6-APA in membrane bioreactor is basically a combination of two processes : enzymatic hydrolysis and ultrafiltration. The hydrolysis of pen-G by penicillin acylase is a reversible reaction and is known to be inhibited competitively by 6-APA and noncompetitively by the other product, namely phenilacetic acid (PAA). The high conversion could be preferably achieved by carrying out the reaction in a homogeneous system using enzyme in a free form, provided that : (a) the enzyme can be effectively retained in the bulk reaction solution and (b) the products can be preferentially removed. Membrane bioreactor is thought to be one which fits these requirements. A serious problem often encountered with the convensional membrane bioreactor, where the driving force for the fermeation flow is due to the applied pressure across the membrane, is the accumulation of enzyme next to membrane surface, which is known as concentration polarization. This tends to degrade the performance of the membrane bioreactor for two reasons : (a) reducing the amount of enzyme in the bulk solution where reaction is supposedly to occur effectively and (b) blocking the membrane surface and thus reducing the permeation flow. One of the ways to reduce this polarization effect is to apply an electric field across the membrane. The enzyme, because of its amphoteric nature, carries electric charge in the solution of pH other than its isoelectric point and tends to migrate in the presence of electric field. This phenomenon is known as electrophoresis. The electrophoretic migration of the enzyme in a direction opposite to the permeate flow will prevent the enzyme from polarizing on the membrane surface. As a consequence, the enzyme can be utilized more efficiently in the bulk solution for reaction.When the enzymatic product is electrically charged, the applied electric field can also be used to accelerate the removal of product from the bioreactor into the permeate stream. The transport rate of the electrically charged product through the membrane can be increased by the electric field. Thus, the permeate stream will be enriched with the product. In this case the simultaneous product separation and concentration is achieved. If the enzymatic reaction is inhibited by the product or the reaction is reversible, the preferential removal of the charged product by the electric field will increase the reaction rate. Consequently, the productivity of the membrane bioreactor will be improved. In this research, continuous pen-G hydrolysis by penicillin acylase was carried out in a membrane bioreactor in the presence of electric field. At the optimum reaction condition, the product, 6-APA, is negatively charged. This hypothesis was tested in this research with a model reaction system of hydrolysis of benzylpenicillin by penicillin acylase enzyme to produce 6-APA and PAA. Since both enzyme and products in the hydrolysis of pen-G can be found as charged molecules, there will be a range of operation conditions where the application of electric field across the membrane will not only generate electrophoretic migration of enzyme away from membrane surface to bulk solution, but also stimulate preferential removal of the of the charged products. The selection of the production of 6-APA through enzymatic conversion of pen-G by enzyme PA is also based on the following consideration. At international level, constant efforts are being made to improve the 6-APA technology at every step. 6-APA is the key raw material for the production of semisynthetic penicillins. The world production of 6-APA is estimated to increase from 7000 tons in 2000 to about 10500 tons in the year 2010. This is primarily because ampicillin, amoxycillin, and other semisynthetic penicillin continue to find wide application as therapeutic agents of choice. The unique feature of this research is the introduction of electrophoretic migration as a technique to improve the productivity of homogeneous enzymatic reaction in a membrane bioreactor. Compared to commercial immobilized enzymebioreactors which are usually hampered by mass transfer limitation and laborious chemical and physical immobilization problems, this electrophoresis coupled membrane bioreactor has shown a better peformance resulting from (a) the effective use of enzyme activity due to the retention of most of the enzyme in the bulk reaction solution and (b) preferential and immediate removal of the products which otherwise their accumulation in the bioreactor will inhibit the reaction. This research was carried out in two complementary stages : theoretical work and experimental work. The main objective of the theoretical work is to build a mathematical model representing the underlying process of pen-G hydrolysis by penicillin acylase in a membrane bioreactor coupled with electrophoresis. The model will then be used to simulate the performance of the membrane bioreactor from which the effect of electric field and optimal operation condition of the bioreactor can be explored. A very important information resulted from the theoretical work would be the determination of optimal dilution rate profile. Following this profile, operation of the membrane bioreactor will be directed to the maximum productivity in a certain period of operation time which usually by the stability of the enzyme. The main objective of the experimental work is to generate data for the expected performance enhancement of the membrane bioreactor due to the coupling of electrophoresis. This data was reported in the form of time course of : concentration of 6-APA in the permeation flow in the absence and presence of electrophoresis, permeate fluks, and enzyme stability. All experiments were carried out in a special membrane bioreactor system. The principal component of this system is the plexiglass membrane bioreactor that have been designed and fabricated at the Department of Chemical Engineering, Faculty of Industrial Technology, Institut Teknologi Bandung. The cell assembly consists of two electrode compartments and one permeate compartment. The permeate stream was separated from the bottom electrode compartment by a cellophane film. The top electrode compartment and the reaction solution in the cell were also separated by a cellophane film. A P020F membrane (Nadir Filtration GmbH) was used throughout the experiments. The molecular weight cutoff of P020F membrane (membrane surface area 50.26 cm2) was reported by the manufacturer to be 20 kDa. The volume of this bioreactor is approximately 300 mL. A mathematical model was developed to describe the particle transport through charged membrane pore under the influence of external electrical field and pressure driven flow. Based on Nernst-Planck and hydrodynamic model equations and the use of Debye-Huckel and center line approximation for interaction potential energy calculation, the model was solved to obtain a compact expression of actual sieving coefficient as a function of electric field strength and trans membrane pressure. From this expression , other performance parameters could be derived, such as permeate concentration, purity, selectivity, and productivity. This model was validated with the experimental data and was then used to simulate the performance of electrofiltration for single and solution mixture. It was shown from the simulation that the increase in operating pressure was decreases the permeate concentration, increases the flux, and decreases the sieving coefficient. Meanwhile, the increase in the electric field strength from negative to positive polarities can increase permeate concentration, decreases the flux, and increases the sieving coefficient. In the case of separation of the reaction mixture, the increase in the electric field strength and the decrease in the operating pressure can cause the increase in separation factor and purity of reaction product. Validation of membrane bioreactor model employed in this work has been done by the use of data obtained from the enzymatic hydrolysis of penicillin G in the ultrafiltration membrane bioreactor using penicillin G acylase, and the literature data. Experimental data were compared to those predicted by the model using parameter such as the Michaelis-Menten constants, inhibition constants, and the permeation rate constants. Fairly good agreement was found between the theoretical analyses and the experimental data. However, the simulation results show that the performance of membrane bioreactor is low due to polarization concentration. By using the membrane bioreactor model which have been tested, electrophoresis phenomena was applied into the bioreactor system that carries out the penicillin G hidrolysis by penicillin acylase. The results indicate that the electrophoresis phenomena applied in the membrane bioreactor system can increase membrane bioreactor performance which is expressed in the reaction conversion, purity of product, and productivity of bioreactor. It is also observed that the higher the electrophoresis effect is applied, the lower the substrate concentration in the permeate compartment. Low substrate concentration in the permeate compartment is one of the cause of the high product purity. Compared to continuous conventional bioreactor systems, continuous membrane bioreactor systems gave a higher conversion, purity, and productivity. The experimental results indicates that the membrane bioreactor systems without electrophoresis increases the reaction conversion, product purity, and productivity of convensional bioreactor system by 3.67%, 73.21%), and 23.25% respectively. An electric field applied to the membrane bioreactor systems can increase its conversion, purity, and productivity. The application of an electric field of 1250 Vim, for example, have increased bioreactor conversion by 50.59%, have increased product purity by 35.05%, and have increased productivity by 34.65% relative to those given by membrane bioreactor systems in the absence of electrophoresis. In general the results of this research will have significant contribution to the development of a method for more effectively conducting homogeneous enzyme catalyzed reaction.